A New Predictor for Patients with Cardiac Implantable Electronic Device in Iatrogenic Pneumothorax: The Clavicle Length Index - Demirtaş, Abdullah Orhan; İçen, Yahya Kemal; Dönmez, Esra; Özsoy, İbrahim Ethem; Koca, Hasan; Karataş, Fadime; Koç, Mevlüt (European Journal of Therapeutics, 2023)
Objective: Pneumothorax (PTX) is a complication that occurs while placing cardiac implantable electronic devices (CIED) in the thorax. In the literature, no clear relationship has been identified between the patient’s anatomic structure and the occurrence of PTX. We aim to investigate whether there is a relationship between PTX and anatomic structure in patients with CIED. Methods: We retrospectively included 1602 patients in whom CIED had been placed for any reason between June 2008 and June 2018. The proximal clavicle tip, middle point, distal tip, and angulus mandible were marked and distances between these points were measured. The ratio between body mass index (BMI) and clavicle length was obtained (clavicle length index). Results: We included 1568 (97.8%) patients without PTX and 34 (2.2%) patients with PTX in our study. The length of the clavicle and the distance between angulus mandible and clavicle middle point, angulus mandible, and clavicle distal tip significantly decreased, while the clavicle length index (CLI) significantly increased in PTX patients. The distance between angulus mandible and clavicle distal tip (OR: 0.811) and CLI (OR: 8.014) were determined to be independent predictors for pneumothorax. When the cut-off value for CLI was taken as 1.67, it was observed that PTX was predicted with 70% sensitivity and 62% specificity. Conclusion: The operator can predict the PTX in the patient by measuring the length of the clavicle and the BMI.